Defense spending and economic growth in Asian economies: A panel error-correction approach - Muzafar Shah, Habibullah; Law, Siong-Hook; Dayang Affizzah, Awang Marikan (Munich University Library, 2008)
Hoping to contribute to the existing pool of literature, this paper examines the relationship between military expenditure and economic growth in selected Asian countries for the period 1989 to 2004. Our panel unit root test suggests that real GDP per capita and military expenditures are I (1) processes, while the Larsson et al. (2001) panel cointegration test indicates that economic growth and military expendirues are cointegrated. Finally, applying the panel error-correction technique proposed by Pesaran et al. (1999), our empirical results show that defense spending and economic growth in the Asian countries under the period of study are not related.